Transport mode use during the COVID-19 lockdown period in Germany: The car became more important, public transport lost ground - Eisenmann, Christine; Nobis, Claudia; Kolarova, Viktoriya; Lenz, Barbara; Winkler, Christian (Transport policy, 2021)
As a result of the coronavirus pandemic, in spring 2020 numerous protective measures were taken in Germany and all over the world. This has changed our everyday life and our mobility considerably. It is in question whether and how the pandemic and the lockdown have impacted transport mode use, attitudes towards transport modes and the ownership of individual mobility options during the lockdown period. In order to shed light on these essential aspects of transport policy, we carried out a representative travel survey in Germany during the strictest period of lockdown in the beginning of April. We have analysed overall and individual changes in transport mode usage and attitudes towards transport modes, focussing on the bicycle, the car and public transport. Also, the changes in the perception of individual mobility options with a focus on car-free households were investigated. Our results indicate that public transport lost ground during the particularly restricted period of lockdown while individual modes of transport, especially the private car, became more important. Our findings are highly relevant for transport policy when developing measures for expanding the possibilities for sustainable individual transport and developing concepts that strengthen public transport. These aspects are key for achieving a sustainable transport system in the medium- and long-term despite the coronavirus pandemic. •We conducted a representative travel survey during the particularly restricted period of lockdown in Germany.•Fewer people had the public transport and the bicycle in their choice set; the share of car users remained stable.•Respondents felt less comfortable using public transport during the lockdown while the car showed a “feel-good” factor.•One third of the members of car-free households miss having a car in the corona pandemic.